Polyvinylidene fluoride-engineered anion exchange membrane for efficient acid enrichment via electrodialysis: Balancing enrichment and non-ideal transport effects - Anuradha; Ritika Sharma; Pooja R. Vishwakarma; Uma Chatterjee; Suresh K. Jewrajka (Desalination, 2026)

Saroglitazar, a novel PPAR-α/γ agonist, modulates thyroid hormone homeostasis through hepatic UGT expression in wistar rats - Praveen Kumar Jain; Laxit K. Bhatt; Ashvin K. Patel; Satyam Patel; Kalpesh Z. Patani; Rajesh J. Patel; Pankaj Dwivedi; Shekhar B. Kadam; Ramchandra K. Ranvir; Hiren M. Patel; Abhijit Chatterjee; Laxmikant Gupta; et al. (Chemico-Biological Interactions, 2026)

A modelling approach to ascertain the memory induced by Findlater Jet in the Arabian Sea - Vikas Kumar Kushwaha; S Prasanna Kumar; F Feba; Lakshmi R. Shenoy; Abhisek Chatterjee; Ashok Karumuri (Climate Dynamics, 2026)
The formation of Findlater Jet (FJ) in the lower atmosphere over the Arabian Sea (AS) is an integral part of the Indian summer monsoon (ISM, June–September). Based on observations, our earlier study indicated that the FJ-induced heat signal during the ISM is potentially preserved in the upper ocean in the form of heat content in the southern AS until the following winter season. Through various sensitivity experiments with an ocean model, we could demonstrate the above and identify the processes that lead to the observed memory. We further demonstrate that the simulated mixed layer depth and the upper ocean heat content are higher in the southern AS during a flood monsoon year compared to a drought year. This is attributed to a relatively stronger FJ-induced wind stress curl during the flood summer monsoon, which deepens the thermocline and results in higher heat retention in the southern AS during the subsequent winter and spring seasons. The accumulated heat enhances pre-monsoon rainfall over the west Indian coastal region and, in turn, influences the ensuing monsoon rainfall.

Effects of elevated temperatures on oxidative stress, antioxidant and biochemical responses in the azooxanthellate coral Tubastraea aurea - Murugan Vasanthakumaran; Julia R. Beaudoin; Li-Chun Tseng; Jishnu Panamoly Ayyappan; Yi-Ta Shao; Mathan Ramesh; Tamilselvan Hema; Triparna Chatterjee; Subramani Thirunavukkarasu; Jiang-Shiou Hwang (Frontiers in Marine Science, 2026)
Introduction Coral reefs are highly productive marine ecosystems that support biodiversity, nutrient cycling, and coastal protection. Thermal stress associated with ocean warming threatens coral physiology by disrupting metabolism, antioxidant defenses, and tissue integrity. Tubastraea aurea , a stony coral with fleshy polyps and a calcareous skeleton, was investigated to determine how increasing temperature affects biochemical composition, oxidative stress responses, and morphological condition under controlled laboratory conditions. Methods Coral colonies were exposed to three temperature regimes, 21 °C, 25 °C, and 29 °C, to evaluate thermal stress effects. Biochemical parameters, including protein and glucose concentrations, were analyzed together with antioxidant biomarkers such as superoxide dismutase, catalase, glutathione S-transferase, and lipid peroxidation. Morphological observations were also conducted to assess tissue coverage, skeletal appearance, and overall physiological condition. Results Protein and glucose levels showed moderate alterations across temperature treatments, although statistical significance was not detected. Reductions were limited at 25 °C but became pronounced at 29 °C, suggesting disruption of protein synthesis and carbohydrate metabolism. Corals maintained at 21 °C and 25 °C retained healthy tissue coverage, whereas specimens exposed to 29 °C displayed darkened skeletal walls and restricted living tissue, indicating severe physiological damage. Antioxidant enzyme activities changed significantly under thermal stress. Superoxide dismutase activity increased progressively with temperature, reflecting enhanced reactive oxygen species production. Catalase activity rose at 21 °C and 25 °C, indicating adaptive detoxification responses. Lipid peroxidation levels increased under all temperature conditions, demonstrating oxidative membrane damage. Glutathione S-transferase activity also increased with temperature, confirming activation of cellular detoxification pathways. Discussion The findings demonstrate that sustained warming negatively affects the stability, antioxidant balance, and morphology of T. aurea . Elevated temperature redirected metabolic energy toward stress defense mechanisms instead of growth, tissue maintenance, and skeletal development. Increased antioxidant enzyme activities and lipid peroxidation confirmed the occurrence of oxidative stress and cellular damage under high temperature exposure. The severe tissue degradation observed at 29 °C suggests reduced coral resilience and highlights the potential consequences of ocean warming for coral survival, function, and persistence.

Seismic Site Classification, Stratigraphy Assessment and SPT-Vs Correlation for Madhubani and Adjoining Regions of Bihar Based on In-Situ Geotechnical and MASW Investigations - Abhileen Chatterjee; Hrik Chaudhury; R. V. S. Jenny Laura; Aman Alok; Abhishek Kumar (Geotechnical and Geological Engineering, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Advanced workflows for UAV-based crop height estimation using structure from motion (SfM) point clouds - Sumantra Chatterjee; Bala Ram Sapkota; Gurjinder S. Baath; K. Colton Flynn; Douglas R. Smith (Remote Sensing Applications: Society and Environment, 2026)

Beyond the target: the ecotoxicological impact of flubendiamide in natural ecosystems - T. Roy; S. Ghosh; A. H. Mandal; N. C. Saha; S. Chatterjee; D. S. Paria; C. R. Multisanti; C. Faggio; S. Saha (International Journal of Environmental Science and Technology, 2026)

Genome Wide Identification, Expression Profiles and Regulatory Network Analysis of SOS Group of Genes in Camellia Sinensis - Surjit Bhattacharjee; Abhirup Paul; Aradhana Jana; Deepak R; G. Meher Unnati; Wang Li; Archita Chatterjee; Chen Lin; Guoxin Shen; Neelam Mishra (Tropical Plant Biology, 2025)

Enhancing LAI estimation using multispectral imagery and machine learning: A comparison between reflectance-based and vegetation indices-based approaches - Sumantra Chatterjee; Gurjinder S. Baath; Bala Ram Sapkota; K.Colton Flynn; Douglas R. Smith (Computers and Electronics in Agriculture, 2025)

Identifying differential survival, photolocomotor behavior, and gene expression responses to cylindrospermopsin in Danio rerio and Pimephales promelas - Kendall R. Scarlett; Laura M. Langan; Lea M. Lovin; Abigail N. Henke; Sujin Kim; Kevin M. Stroski; C. Kevin Chambliss; Saurabh Chatterjee; J. Thad Scott; Bryan W. Brooks (Science of The Total Environment, 2025)

Mercury speciation in a complex tropical estuarine system: Understanding natural and anthropogenic influences - Prasad P. Padalkar; Parthasarathi Chakraborty; Soham Chatterjee; Debashish Pradhan; Deepak R. P; Arindam Sarkar; Saranya Jayachandran (Regional Studies in Marine Science, 2025)

Shelf-life extension of ready-to-cook Tilapia (Oreochromis spp.) fish balls using hurdle technology - Raj Kamal Gautam; Aarti S. Kakatkar; Ashika Debbarma; Prashant K. Mishra; Vivekanand Kumar; R Shashidhar; Suchandra Chatterjee (Food Bioscience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Large scale screening and quantification of micropollutants in fish from the coastal waters of Cochin, India: Analytical method development and health risk assessment - Nasreen Nazar; A.S. Athira; R. Devi Krishna; Satyen Kumar Panda; Kaushik Banerjee; Niladri Sekhar Chatterjee (Science of The Total Environment, 2024)

Endoscopic screening for identification of signet ring cell gastric cancer foci in carriers of germline pathogenic variants in CDH1 - Lady Katherine Mejia Perez; Margaret O’Malley; Arjun Chatterjee; Ruishen Lyu; Qijun Yang; Michael W. Cruise; Lisa LaGuardia; David Liska; Carole Macaron; R. Matthew Walsh; Carol A. Burke (Familial Cancer, 2024)
To determine the preoperative detection of signet ring cancer cells (SRC) on upper endoscopy (EGD) in patients with CDH1 pathogenic variant (PV) undergoing gastrectomy. To evaluate the development of advanced diffuse gastric cancer (DGC) in patients choosing surveillance. Guidelines recommend prophylactic total gastrectomy (pTG) in CDH1 PV carriers with family history of DGC between 18 and 40 years. Annual EGD with biopsies according to established protocols is recommended in carriers with no SRC and no family history of DGC, with consideration of pTG. Retrospective analysis of asymptomatic patients with CDH1 PVs with ≥ 1 surveillance EGD. Outcomes included pre-operative EGD detection of SRC, surgical stage, and progression to advanced DGC in those electing surveillance with EGD. 48 patients with CDH1 PVs who had ≥ 1 EGD were included. 24/ 48 (50%) underwent gastrectomy, including pTG in 7 patients. SRCC were detected on gastrectomy specimen in 21/24 (87.5%). SRCs were identified by EGD in 17/21 patients who had SRCC on gastrectomy specimens (sensitivity 81%, 17/21). All cancers were stage pT1a. The remaining 17 patients (50% with a family history of gastric cancer) continue in annual EGD surveillance with a median follow-up of 34.6 months. No SRCC or advanced DGC have been diagnosed. No CDH1 PV carriers without SRCC on random biopsies followed in an endoscopic program developed advanced DGC over a median follow up of 3 years. In the short term, EGD surveillance might be a safe alternative to immediate pTG in experienced hands in referral centers.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

LP-12 Behavioral alterations by micro(nano) plastics: insights from Zebrafish and Caenorhabditis elegans - C. Kempkens Palacios; J. Le Du-Carrée; R. Almeda; S.H. Keiter; E. Alfaro-Moreno; N. Chatterjee (Toxicology Letters, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Assessment of groundwater level using satellite-based hydrological parameters in North-West India: A deep learning approach - Pranshu Pranjal; Dheeraj Kumar; Ashish Soni; R. S. Chatterjee (Earth Science Informatics, 2024)

A review on environmental impacts of renewable energy for sustainable development - D. Gayen; R. Chatterjee; S. Roy (International Journal of Environmental Science and Technology, 2024)

Metal Contamination of Different Water Categories and Surface Soil Near Thermal Power Plants at Varied Geographic Sites of India and Their Health Risk Assessment - Khaiwal Ravindra; Nitasha Vig; Neha Agarwal; Vivek Singh Malik; Elangovan Arumugam; Prabu Rajkumar; Elavarasu Govindasamy; Punita Kumar; Prabir Chatterjee; Ramachandra Kamath; Surekha R Kamath; Sharvanan E. Udayar; et al. (Water, Air, & Soil Pollution, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Characteristics of mean and extreme precipitation in Ny Ålesund, Arctic - R. Athulya; M. Nuncio; Sourav Chatterjee; P.J. Vidya (Atmospheric Research, 2023)

Unravelling the dynamics and causes of land subsidence in the National Capital Territory of Delhi, India, by spaceborne and in situ observations - R. S. Chatterjee; Pranshu Pranjal; Suresh Kannaujiya; Shailaja Thapa; Ashutosh Bhardwaj; Uma Kapoor; S. N. Dwivedi; Rajesh Chandra; Rajiv Kumar Srivastava; S. K. Singh; Harsh Kumar; Rajarshi Bhattacharjee; et al. (Bulletin of Engineering Geology and the Environment, 2023)

An evolving perspective on the fluoride mitigation techniques - S. K. Das; A. K. Pramanik; R. K. Das; A. Chatterjee (International Journal of Environmental Science and Technology, 2023)

The transposable element-derived transcript of LIN28B has a placental origin and is not specific to tumours - Chiemi F. Lynch-Sutherland; Lorissa I. McDougall; Peter A. Stockwell; Suzan N. Almomani; Robert J. Weeks; Jackie L. Ludgate; Teena K. J. B. Gamage; Aniruddha Chatterjee; Joanna L. James; Michael R. Eccles; Erin C. Macaulay (Molecular Genetics and Genomics, 2023)
Transposable elements (TEs) are genetic elements that have evolved as crucial regulators of human development and cancer, functioning as both genes and regulatory elements. When TEs become dysregulated in cancer cells, they can serve as alternate promoters to activate oncogenes, a process known as onco-exaptation. This study aimed to explore the expression and epigenetic regulation of onco-exaptation events in early human developmental tissues. We discovered co-expression of some TEs and oncogenes in human embryonic stem cells and first trimester and term placental tissues. Previous studies identified onco-exaptation events in various cancer types, including an AluJb SINE element– LIN28B interaction in lung cancer cells, and showed that the TE-derived LIN28B transcript is associated with poor patient prognosis in hepatocellular carcinoma. This study further characterized the AluJb– LIN28B transcript and confirmed that its expression is restricted to the placenta. Targeted DNA methylation analysis revealed differential methylation of the two LIN28B promoters between placenta and healthy somatic tissues, indicating that some TE–oncogene interactions are not cancer-specific but arise from the epigenetic reactivation of developmental TE-derived regulatory events. In conclusion, our findings provide evidence that some TE–oncogene interactions are not limited to cancer and may originate from the epigenetic reactivation of TE-derived regulatory events that are involved in early development. These insights broaden our understanding of the role of TEs in gene regulation and suggest the potential importance of targeting TEs in cancer therapy beyond their conventional use as cancer-specific markers.

Hails in Ny Alesund, Svalbard-atmospheric vertical structure and dependence on circulation - M. Nuncio; R. Athulya; Naveen Nandanan; Sourav Chatterjee; K. Satheesan; Asutosh Acharya; M. P. Subeesh; P. J. Vidya (Natural Hazards, 2023)
Hails observed at Ny Alesund, Svalbard in the Arctic during December–February 2018–19 is examined along with the atmospheric circulation patterns. When hail was noticed, surface warming and southwesterly—westerly winds were noticed. Atmospheric circulation pattern was characterised by high pressure anomaly over northwestern Europe. High clouds as well as excess liquid water were present when the high pressure systems were active over northwestern Europe. This is because winds blowing over ocean collect more moisture as well as transport nucleating particles to Svalbard. Also, hourly winds from ERA 5 reanalysis indicated vertical shear required for hail formation. When hails were observed, mixed precipitation types were recorded with the maximum intensities arising from the hails. The West Spitzbergen Current (WSC) induces a strong east west sea surface temperature (SST) gradient in the ocean west of Svalbard. A corresponding gradient in the atmospheric temperature is also maintained by the WSC in the west to east direction in the lower atmosphere. Moisture laden westerlies cross the SST gradient and induce strong frontal activity in the lower atmosphere resulting intense precipitation and hail. The upward vertical velocity noted in the lower troposphere supports the frontal activity. Human activities in the Arctic as elsewhere are bound to increase. Hence, there is a need to study the intense precipitation in the Arctic as well as its reasons as it can impact the Arctic environment and human activity. This calls for more continuous observations to clearly identify mechanisms and frequency of intense precipitation in the Arctic.

Agronomic manipulation in main season and ratoon rice influences growth, productivity, and regeneration ability in tropical lowlands - B. Lal; Priyanka Gautam; A.K. Nayak; R. Raja; B.B. Panda; R. Tripathi; M. Shahid; D. Chatterjee; P. Bhattacharyya; P. Bihari; Teekam Singh; S.K. Meena; et al. (Field Crops Research, 2023)

Hydrated komatiites as a source of water for TTG formation in the Archean - R. Tamblyn; J. Hermann; D. Hasterok; P. Sossi; T. Pettke; S. Chatterjee (Earth and Planetary Science Letters, 2023)

Magmatic inflation, miniature dyke intrusion and prolonged torrential rainfall led to the emergence of the 2018 aseismic fissure in Kenya - R. S. Chatterjee; Kishan Kumar; Pranshu Pranjal; Suresh Kannaujiya; Prakash Chauhan (Natural Hazards, 2023)

Lifestyle, Epstein-Barr virus infection, and other factors could impede nasopharyngeal cancer survivorship: a five-year cross-sectional study in North Eastern India - Koustav Chatterjee; Sankar Deb Roy; Koushik Chakraborty; Asmaul Haque; Sudipta Chakrabarti; Syamantak Mukherjee; Sudipa Mal; Nilanjana Das; Sushil Kumar Sahu; Nabanita Roy Chattopadhyay; Piyanki Das; R. Rajendra Reddy; et al. (VirusDisease, 2022)

Phlorotannins–bioactivity and extraction perspectives - Lekshmi R. G. Kumar; Preethy Treesa Paul; K. K. Anas; C. S. Tejpal; N. S. Chatterjee; T. K. Anupama; Suseela Mathew; C. N. Ravishankar (Journal of Applied Phycology, 2022)

Mineral magnetic and geochemical characterization of the dust and soils around Mejia Thermal Power Plant, West Bengal: Implications to source apportionment - Rimjhim Maity; M Venkateshwarlu; Supriya Mondal; M R Kapawar; Debesh Gain; Saurodeep Chatterjee; Punyotoya Paul (Journal of Earth System Science, 2022)

Relic surface water (clay-pore water) input triggers arsenic release into the shallow groundwater of Bengal aquifers - Pousali Pathak; Prosenjit Ghosh; Sanchita Banerjee; R S Chatterjee; Noor Muzakkira; Pradip K Sikdar; Utsab Ghosal; Mao-Chang Liang; Kathiravan Meeran (Journal of Earth System Science, 2022)

Marine heatwaves in the Arabian Sea - Abhisek Chatterjee; Gouri Anil; Lakshmi R. Shenoy (Ocean Science, 2022)
Marine heatwaves (MHWs) are prolonged warm sea condition events that can have a destructive impact on marine ecosystems. The documentation of MHWs and assessment of their impacts is largely confined to a few regional seas or to global mean studies. The north Indian Ocean received almost no attention in this regard despite the fact that this ocean basin, particularly the Arabian Sea, has been warming at the most rapid pace among the other tropical basins in recent decades. This study shows the characteristics of MHW events for the Arabian Sea during 1982–2019. Our analysis shows that the duration (frequency) of MHWs exhibits a rapidly increasing trend of ∼20 d per decade (1.5–2 events per decade) in the northern Arabian Sea and the southeastern Arabian Sea close to the west coast of India, which is a multifold increase in MHW days (frequency) from the 80s. Notably, since the beginning of the satellite record, the years 2010 and 2016 have exhibited the maximum number of heatwave days when more than 75 % of days of the pre-monsoon and summer monsoon season experience heatwaves. The accelerated trend of the heatwave days is found to be driven by the rapid rise in the mean sea surface temperature (SST) of the Arabian Sea in the recent decade. Moreover, longer heatwave days are also associated with dominant climate modes. Among them, the Indian Ocean Basin Mode via the decaying phase of El Niño is the most influential mode contributing to more than 70 %–80 % of observed heatwave days in this basin. Further analysis of the most prolonged observed heatwave during April–June 2010 indicates that surface heat flux associated with the weaker latent heat loss and the shallow mixed layer was the primary cause of this event. Further, we note that the pre-monsoon cyclonic storms in the Arabian Sea often contribute to the waning of such heatwaves in the basin.

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Seasonal Transport Pathway and Sources of Carbonaceous Aerosols at an Urban Site of Eastern Himalaya - Akansha Rai; Sauryadeep Mukherjee; Nikki Choudhary; Abhinandan Ghosh; A. Chatterjee; T. K. Mandal; S. K. Sharma; R. K. Kotnala (Aerosol Science and Engineering, 2021)

Genome‐wide variation in DNA methylation linked to developmental stage and chromosomal suppression of recombination in white‐throated sparrows - Dan Sun; Thomas S. Layman; Hyeonsoo Jeong; Paramita Chatterjee; Kathleen Grogan; Jennifer R. Merritt; Donna L. Maney; Soojin V. Yi (Molecular Ecology, 2021)
Much of our knowledge on regulatory impacts of DNA methylation has come from laboratory‐bred model organisms, which may not exhibit the full extent of variation found in wild populations. Here, we investigated naturally‐occurring variation in DNA methylation in a wild avian species, the white‐throated sparrow ( Zonotrichia albicollis ). This species offers exceptional opportunities for studying the link between genetic differentiation and phenotypic traits because of a nonrecombining chromosome pair linked to both plumage and behavioural phenotypes. Using novel single‐nucleotide resolution methylation maps and gene expression data, we show that DNA methylation and the expression of DNA methyltransferases are significantly higher in adults than in nestlings. Genes for which DNA methylation varied between nestlings and adults were implicated in development and cell differentiation and were located throughout the genome. In contrast, differential methylation between plumage morphs was concentrated in the nonrecombining chromosome pair. Interestingly, a large number of CpGs on the nonrecombining chromosome, localized to transposable elements, have undergone dramatic loss of DNA methylation since the split of the ZAL2 and ZAL2 m chromosomes. Changes in methylation predicted changes in gene expression for both chromosomes. In summary, we demonstrate changes in genome‐wide DNA methylation that are associated with development and with specific functional categories of genes in white‐throated sparrows. Moreover, we observe substantial DNA methylation reprogramming associated with the suppression of recombination, with implications for genome integrity and gene expression divergence. These results offer an unprecedented view of ongoing epigenetic reprogramming in a wild population.

Hybrid larval lethality of Drosophila is caused by parent-of-origin expression: an insight from imaginal discs morphogenesis of Lhr pausing rescue hybrids of D. melanogaster and D. simulans - R. N. Chatterjee; S. Kuthe; Piyali Chatterje (The Nucleus, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Inheritance of growth traits and impact of selection on carcass and egg quality traits in Vanashree, an improved indigenous chicken - Santosh Haunshi; Rajkumar U.; C. Paswan; L. L. L. Prince; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Use of IRS-1C and Its Follow-On Missions for Geological Applications: A Review - S. K. Srivastav; R. S. Chatterjee; Deepali Kapoor; G. Sreenivasan; E. V. R. Parthasaradhy (Journal of the Indian Society of Remote Sensing, 2021)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

Source-dependent compositional changes in coconut flavoured liquid smoke and its application in traditional Indian smoked fishery products - Nithin C.T.; Niladri Sekhar Chatterjee; Joshy C.G.; Yathavamoorthi R.; Ananthanarayanan T.R.; Suseela Mathew; Bindu J.; Srinivasa Gopal T.K. (Food Additives & Contaminants: Part A, 2020)

Assessing Impacts of Conservation Measures on Watershed Hydrology Using MIKE SHE Model in the Face of Climate Change - Gajanan Ramteke; R. Singh; C. Chatterjee (Water Resources Management, 2020)

Correction to: A machine learning forecasting model for COVID-19 pandemic in India - R. Sujatha; Jyotir Moy Chatterjee; Aboul Ella Hassanien (Stochastic Environmental Research and Risk Assessment, 2020)

Heavy metals in urban road dusts from Kolkata and Bengaluru, India: implications for human health - Simon R. N. Chenery; Santosh K. Sarkar; Mousumi Chatterjee; Andrew L. Marriott; Michael J. Watts (Environmental Geochemistry and Health, 2020)

A machine learning forecasting model for COVID-19 pandemic in India - R. Sujath; Jyotir Moy Chatterjee; Aboul Ella Hassanien (Stochastic Environmental Research and Risk Assessment, 2020)

Bioleaching of heavy metals from spent batteries using Aspergillus nomius JAMK1 - A. Chatterjee; R. Das; J. Abraham (International Journal of Environmental Science and Technology, 2020)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

Ectopic expression of olfactory receptors and associated G‐protein subunits in the head integument of the amphihaline migratory fish hilsa Tenualosa ilisha - Subhendu K. Chatterjee; Chandan Malick; Samir Bhattacharya; Vettath R. Suresh; Rakesh Kundu; Surjya K. Saikia (Journal of Fish Biology, 2019)
The chemosensory nature of the tissue from the dorsal surface of the head (also termed sensory pad; SP) of the amphihaline diadromous fish hilsa Tenualosa ilisha was investigated for odorant receptor (OR), olfactory marker protein (OMP) and G‐protein subunits (Gαs‐olf, Gαq, Gαo, Gαi3) through immunolocalization and immunoblotting techniques. The immunolocalization of OR, OMP and G‐protein subunits showed clear expression of these proteins in the tissues of the SP. Robust expressions of these proteins in the SP were detected with immunoblot analysis. The strong expression of these proteins in the SP indicates that the tissues from this area in riverine T. ilisha may play significant role in chemosensing and signalling through ectopic expression of olfactory receptor proteins which are otherwise reported in olfactory organs in vertebrates. Being migratory in nature, ectopic expression of these receptors in T. ilisha probably helps them to prevent damage to epidermal tissues of the SP, or they may also utilize them as a chemo and mechanosensory tool to optimize chemo‐communications during migration.

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Curcumin ameliorates PRMT5-MEP50 arginine methyltransferase expression by decreasing the Sp1 and NF-YA transcription factors in the A549 and MCF-7 cells - Biji Chatterjee; Krishna Ghosh; Lavanya Suresh; Santosh R. Kanade (Molecular and Cellular Biochemistry, 2019)

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

Assessment of Land Surface Subsidence Due to Underground Metal Mining Using Integrated Spaceborne Repeat-Pass Differential Interferometric Synthetic Aperture Radar (DInSAR) Technique and Ground Based Observations - Md Soyeb Alam; Dheeraj Kumar; R. S. Chatterjee; Vijay Upreti (Journal of the Indian Society of Remote Sensing, 2018)

A Chemosensitizer Drug: Disulfiram Prevents Doxorubicin-Induced Cardiac Dysfunction and Oxidative Stress in Rats - Varsha K. Sonawane; Umesh B. Mahajan; Sachin D. Shinde; Subhajit Chatterjee; Sandip S. Chaudhari; Harshada A. Bhangale; Shreesh Ojha; Sameer N. Goyal; Chanakya N. Kundu; Chandragouda R. Patil (Cardiovascular Toxicology, 2018)

Molecular characterization and expression profiling of BMP 3 gene in broiler and layer chicken - Devara Divya; Tarun Kumar Bhattacharya; Manthani Gnana Prakash; R. N. Chatterjee; Renu Shukla; Pothana Boyina Guru Vishnu; Amirthalingam Vinoth; Kotha Dushyanth (Molecular Biology Reports, 2018)

Noise Induces Hypothyroidism and Gonadal Dysfunction Via Stimulation of Pineal–Adrenal Axis in Chicks - Prajna Paramita Ray; Tania Chatterjee; Sraboni Roy; Suvojit Rakshit; Madhumita Bhowmik; Jaysree Guha; Aniruddha Maity; Indraneel Saha; Ankur Bhowal; Aniruddha Chatterjee; Supriti Sarkar; Debabrata Nag; et al. (Proceedings of the Zoological Society, 2018)

Dosage compensation and its roles in evolution of sex chromosomes and phenotypic dimorphism: lessons from Drosophila, C.elegans and mammals - R. N. Chatterjee (The Nucleus, 2017)

Evaluation of the oncolytic potential of R2B Mukteshwar vaccine strain of Newcastle disease virus (NDV) in a colon cancer cell line (SW-620) - Kishan K. Sharma; Irsadullakhan H. Kalyani; Jogeswar Mohapatra; Satish D. Patel; Dharmesh R. Patel; Priti D. Vihol; Abhijit Chatterjee; Dinesh R. Patel; Bhavesh Vyas (Archives of Virology, 2017)

Erratum to: Inhibition of mixed-layer deepening during winter in the northeastern Arabian Sea by the West India Coastal Current - D. Shankar; R. Remya; P. N. Vinayachandran; Abhisek Chatterjee; Ambica Behera (Climate Dynamics, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Sequence Determination of an Antioxidant Peptide Obtained by Enzymatic Hydrolysis of Oyster Crassostrea madrasensis (Preston) - K. K. Asha; K. R. Remya Kumari; K. Ashok Kumar; Niladri S. Chatterjee; R. Anandan; Suseela Mathew (International Journal of Peptide Research and Therapeutics, 2016)

Inhibition of mixed-layer deepening during winter in the northeastern Arabian Sea by the West India Coastal Current - D. Shankar; R. Remya; P. N. Vinayachandran; Abhisek Chatterjee; Ambica Behera (Climate Dynamics, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Functional Screening and Molecular Characterization of Halophilic and Halotolerant Bacteria by 16S rRNA Gene Sequence Analysis - Bijay Kumar Behera; Priyanka Das; Jitendra Maharana; Dharmendra Kumar Meena; Tanmaya Kumar Sahu; A. R. Rao; Soumendranath Chatterjee; Bimal Prasanna Mohanty; Anil Prakash Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Detecting, mapping and monitoring of land subsidence in Jharia Coalfield, Jharkhand, India by spaceborne differential interferometric SAR, GPS and precision levelling techniques - R S Chatterjee; Shailaja Thapa; K B Singh; G Varunakumar; E V R Raju (Journal of Earth System Science, 2015)

Intersex (ix) mutations of Drosophila melanogaster cause nonrandom cell death in genital disc and can induce tumours in genitals in response to decapentaplegic (dpp disk ) mutations - R. N. CHATTERJEE; P. CHATTERJEE; S. KUTHE; M. ACHARYYA-ARI; R. CHATTERJEE (Journal of Genetics, 2015)

Tipping off endothelial tubes: nitric oxide drives tip cells - Mani Krishna Priya; Giriraj Sahu; David R. Soto-Pantoja; Naga Goldy; Abaya Meenakshi Sundaresan; Vivek Jadhav; T. R. Barathkumar; Uttara Saran; B. M. Jaffar Ali; David D. Roberts; Amal Kanti Bera; Suvro Chatterjee (Angiogenesis, 2015)

Cloning, characterization and expression of myostatin (growth differentiating factor-8) gene in broiler and layer chicken (Gallus gallus) - T. K. Bhattacharya; R. N. Chatterjee; K. Dushyanth; R. Shukla (Molecular Biology Reports, 2015)

Role and Present Status of Biotechnology in Augmenting Poultry Productivity in India - C. Paswan; T. K. Bhattacharya; C. S. Nagaraj; R. N. Chatterjee; P. Guru Vishnu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Managing the Indian coast in the face of disasters & climate change: a review and analysis of India’s coastal zone management policies - R. R. Krishnamurthy; Rajarshi DasGupta; Ranit Chatterjee; Rajib Shaw (Journal of Coastal Conservation, 2014)

The high prevalence of serine protease autotransporters of Enterobacteriaceae (SPATEs) in Escherichia coli causing neonatal septicemia - R. Tapader; S. Chatterjee; A. K. Singh; P. Dayma; S. Haldar; A. Pal; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Traditional and targeted exome sequencing reveals common, rare and novel functional deleterious variants in RET-signaling complex in a cohort of living US patients with urinary tract malformations - Rajshekhar Chatterjee; Enrique Ramos; Mary Hoffman; Jessica VanWinkle; Daniel R. Martin; Thomas K. Davis; Masato Hoshi; Stanley P. Hmiel; Anne Beck; Keith Hruska; Doug Coplen; Helen Liapis; et al. (Human Genetics, 2012)

Unsupervised and supervised classification of hyperspectral imaging data using projection pursuit and Markov random field segmentation - A. Sarkar; A. Vulimiri; S. Paul; Jawaid Iqbal; A. Banerjee; R. Chatterjee; S. S. Ray (International Journal of Remote Sensing, 2012)

Evolutionary origin of chromatin remodeling for dosage compensation: Lessons from epigenetic modifications of X chromosomes in germ cells of Drosophila, C.elegans and Mammals - R. N. Chatterjee; Piyali Chatterjee (The Nucleus, 2012)

Acute and chronic effects of endosulfan on the haemato-immunological and histopathological responses of a threatened freshwater fish, spotted murrel, Channa punctatus - Kamal Sarma; A. K. Pal; N. P. Sahu; R. S. Dalvi; Nirupama Chatterjee; S. C. Mukherjee; Kartik Baruah (Fish Physiology and Biochemistry, 2012)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Exploring Granger causality between global average observed time series of carbon dioxide and temperature - Evan Kodra; Snigdhansu Chatterjee; Auroop R. Ganguly (Theoretical and Applied Climatology, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

Differential expression of Toll-like receptor mRNA in White Leghorn and indigenous chicken of India - Kannaki T. Ramasamy; Maddula R. Reddy; Dhanutha N. Raveendranathan; Shanmugam Murugesan; Rudra N. Chatterjee; Rajkumar Ullengala; Santosh Haunshi (Veterinary Research Communications, 2010)

Effect of stocking density and journey length on the welfare of rohu (Labeo rohita Hamilton) fry - N. Chatterjee; A. K. Pal; T. Das; R. Dalvi; M. S. Mohammad; K. Sarma; S. C. Mukherjee; K. Baruah (Aquaculture International, 2010)

The role of post-transcriptional RNA processing and plasmid vector sequences on transient transgene expression in zebrafish - Sumantra Chatterjee; Lin Min; R. Krishna Murthy Karuturi; Thomas Lufkin (Transgenic Research, 2010)

Enhanced expression of α1-acid glycoprotein and fucosylation in hepatitis B patients provides an insight into pathogenesis - Gautam Mondal; Urmimala Chatterjee; Hasi R. Das; Bishnu P. Chatterjee (Glycoconjugate Journal, 2009)

Proctolaclaps regalis usages Drosophila eggs and pupae as ovipositional substrate and their lifecycle closely mimics the life cycle of Drosophila - P. Chatterjee; S. Banerjee; R. N. Chatterjee (Proceedings of the Zoological Society, 2009)

Categorization of environmental sounds - R. K. Reddy; V. Ramachandra; N. Kumar; Nandini Chatterjee Singh (Biological Cybernetics, 2009)

HSV-2 ICP34.5 protein modulates herpes simplex virus glycoprotein processing - Somik Chatterjee; Jason W. Wang; Mary J. Cismowski; John R. Bower; Kenneth Steven Rosenthal (Archives of Virology, 2009)

Flood inundation modeling using MIKE FLOOD and remote sensing data - S. Patro; C. Chatterjee; S. Mohanty; R. Singh; N. S. Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2009)

Assaying Baseline Status of Particulate Laden Polyaromatic Hydrocarbon for a Grass Root Level Industrial Project - Girish Himatlal Pandya; N. Chatterjee; Ritesh Singh; Sanjay Kashyap; S. Pentu Saheb; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2009)

A novel locus DFNA59 for autosomal dominant nonsyndromic hearing loss maps at chromosome 11p14.2–q12.3 - Arunima Chatterjee; Rajeev Jalvi; Nishtha Pandey; R. Rangasayee; Anuranjan Anand (Human Genetics, 2009)

Influence of progressive staling on germination of sugarcane - A. K. Shrivastava; S. Solomon; A. K. Srivastava; S. P. Shukla; A. Sawnani; R. Darash; C. Prajapati; Pushpa Singh; Priyanka Singh; R. K. Rai; R. Jain; Parul Srivastava; et al. (Sugar Tech, 2008)

Utilization of high resolution satellite gravity over the Carlsberg Ridge - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (Marine Geophysical Research, 2007)

Drosophila simulans Lethal hybrid rescue mutation (Lhr) rescues inviable hybrids by restoring X chromosomal dosage compensation and causes fluctuating asymmetry of development - R. N. Chatterjee; P. Chatterjee; A. Pal; M. Pal-Bhadra (Journal of Genetics, 2007)

Generation and study of high‐resolution satellite gravity over the Sumatran earthquake region - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (International Journal of Remote Sensing, 2007)

Activation dependent expression of MMPs in peripheral blood mononuclear cells involves protein kinase A - K. Saja; Urmimala Chatterjee; B. P. Chatterjee; P. R. Sudhakaran (Molecular and Cellular Biochemistry, 2007)

Transgenic Indian mustard (Brassica juncea) expressing tomato glucanase leads to arrested growth of Alternaria brassicae - Kalyan K. Mondal; R. C. Bhattacharya; K. R. Koundal; S. C. Chatterjee (Plant Cell Reports, 2007)

Phytotoxic Effect of Coal Mine Effluent on Growth Behavior, Betabolic Changes, and Metal Accumulation in Rice Plants (Oryza sativa L.) c.v. IR-36 - K. K. Tiwari; S. Dwivedi; U. N. Rai; A. K. Pandey; C. Chatterjee; N. K. Singh; R. D. Tripathi (Bulletin of Environmental Contamination and Toxicology, 2006)

New temperate DNA phage BcP15 acts as a drug resistance vector - D. K. Hens; N. C. Chatterjee; R. Kumar (Archives of Virology, 2006)

Rapid depletion of mutant eukaryotic initiation factor 5A at restrictive temperature reveals connections to actin cytoskeleton and cell cycle progression - Ishita Chatterjee; Stephane R. Gross; Terri Goss Kinzy; Kuang Yu Chen (Molecular Genetics and Genomics, 2006)

Silica and volatile-element metasomatism of Archean mantle: a xenolith-scale example from the Kaapvaal Craton - D. R. Bell; M. Grégoire; T. L. Grove; N. Chatterjee; R. W. Carlson; P. R. Buseck (Contributions to Mineralogy and Petrology, 2005)

The effect of occlusive and unocclusive exposure to xylene and benzene on skin irritation and molecular responses in hairless rats - A. Chatterjee; R. J. Babu; E. Ahaghotu; M. Singh (Archives of Toxicology, 2005)

Development of Regional Flood Frequency Relationships Using L-moments for Middle Ganga Plains Subzone 1(f) of India - Rakesh Kumar; C. Chatterjee; Sanjay Kumar; A. K. Lohani; R. D. Singh (Water Resources Management, 2003)

The flight of Archaeopteryx - Sankar Chatterjee; R. Jack Templin (The Science of Nature, 2003)

Sensitivity Analysis of the GIUH based Clark Model for a Catchment - Rakesh Kumar; C. Chatterjee; A. K. Lohani; Sanjay Kumar; R. D. Singh (Water Resources Management, 2002)

Removal of carboxymethyl cellulase activity from the culture filtrate of Termitomyces clypeatus producing xylanase - A.K. Ghosh; M.L. Jana; A.K. Naskar; R. Chatterjee; S. Sengupta (Biotechnology Letters, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Sunflower Nitrate Reductase: Purification and Characterization - Debasis Pattanayak; Sukumar R. Chatterjee (Journal of Plant Biochemistry and Biotechnology, 1999)

Light-mediated Regulation of Nitrate Reductase in Higher plants - Debasis Pattanayak; Sukumar R. Chatterjee (Journal of Plant Biochemistry and Biotechnology, 1998)

Mildly alkaline basalts from Pavagadh Hill, India: Deccan flood basalts with an asthenospheric origin - J. D. Greenough; K. R. Hari; A. C. Chatterjee; M. Santosh (Mineralogy and Petrology, 1998)

Our experience with experimentalWuchereria bancrofti infection in Indian langur (Presbytis entellus) - Shailja Misra Bhattacharya; K. Tyagi; R. K. Chatterjee (Indian Journal of Clinical Biochemistry, 1997)

Impact of Carbofuran in the Oocyte Maturation of Catfish, Heteropenustes fossilis (Bloch) - S. Chatterjee; A. B. Dutta; R. Ghosh (Archives of Environmental Contamination and Toxicology, 1997)

Lipid peroxidation induced by a novel porphyrin plus light in isolated mitochondria: Possible implications in photodynamic therapy - Shampa R. Chatterjee; T.S. Srivastava; J.P. Kamat; T.P.A. Devasagayam (Molecular and Cellular Biochemistry, 1997)

Zinc and iron as bioindicators of precancerous nature of oral submucuos fibrosis - R. R. Paul; J. Chatterjee; A. K. Das; S. K. Dutta; D. Roy (Biological Trace Element Research, 1996)

Effects of L-ascorbic acid supplementation on dieldrin toxicity in rats - S. K. Bandyopadhyay; R. K. Tiwari; A. Mitra; B. Mukherjee; A. Banerjee; G. C. Chatterjee (Archives of Toxicology, 1982)